2013
DOI: 10.1089/jmf.2013.0043
|View full text |Cite
|
Sign up to set email alerts
|

The I148M Variant of PNPLA3 Reduces the Response to Docosahexaenoic Acid in Children with Non-Alcoholic Fatty Liver Disease

Abstract: The aim of this secondary analysis of a randomized controlled trial was to test whether the I148M variant of Patatin-like phospholipase domain-containing protein-3 (PNPLA3) is associated with the response to docosahexaenoic acid (DHA) in children with non-alcoholic fatty liver disease (NAFLD). Sixty children with NAFLD were randomized in equal numbers to DHA 250 mg/day, DHA 500 mg/day or placebo. Coherently with the primary analysis, the probability of more severe steatosis after 24 months of DHA supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 25 publications
4
36
0
1
Order By: Relevance
“…Thus, it is possible that the lack of response to DHA+EPA treatment in decreasing liver fat % in subjects with PNPLA3 I148 MM could be due to the fact that these subjects already have low levels of de novo lipogenesis. That said, it is not known whether PNPLA3 (I148M) GG genotype affects the incorporation of DHA (or EPA) into the liver lipid droplet, although recent evidence in a small study in children suggests that the PNPLA3 (I148M) GG genotype attenuates the benefit of DHA to decrease liver fat (40). These data in children are in agreement with, and are extended by, our data, showing PNPLA3 (I148M) GG genotype is associated with lower levels of DHA enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the lack of response to DHA+EPA treatment in decreasing liver fat % in subjects with PNPLA3 I148 MM could be due to the fact that these subjects already have low levels of de novo lipogenesis. That said, it is not known whether PNPLA3 (I148M) GG genotype affects the incorporation of DHA (or EPA) into the liver lipid droplet, although recent evidence in a small study in children suggests that the PNPLA3 (I148M) GG genotype attenuates the benefit of DHA to decrease liver fat (40). These data in children are in agreement with, and are extended by, our data, showing PNPLA3 (I148M) GG genotype is associated with lower levels of DHA enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…The PNPLA3-I148M variant hampers triglyceride esterase causing reduced remodelling of lipid droplets in association with excessive intake of carbohydrates or saturated fatty acids and other genetic factors [60][61][62][63]. The association between the I148M variant and NAFLD holds true both in adults and in adolescents [64][65][66][67][68]; I148M allele homozygosity predisposes to NASH and hepatic fibrosis [56][57][58]. The association between the I148M variant and fibrosis is also evident in chronic viral hepatitis and genetic diseases, such as hereditary haemochromatosis [69][70][71].…”
Section: Geneticsmentioning
confidence: 99%
“…Therefore, both PNPLA3-I148M and TM6SF2E167K may be useful in identifying NAFLD patients at a higher risk of hepatic than cardiovascular complications and the PNPLA3-based categorisation of NAFLD may have therapeutic implications. Preliminary data suggest that I148M-homozygous subjects might benefit from weight loss after a short-term low-carbohydrate diet [68,78]; however, disease progression is modulated by multiple environmental and genetic factors [48,[79][80][81][82]. Thus, PNPLA3 I148M and TM6SF2 variants plus/minus a family history for cirrhosis and/or HCC and ethnicity can be used to stratify patients at risk in clinical practice ( Table 2).…”
Section: Geneticsmentioning
confidence: 99%
“…Furthermore, the pathogenesis of NAFLD, and perhaps the response to treatment, is also influenced by different genetic and epigenetic factors, and these factors may profoundly influence the efficacy of specific treatments (129). In support of this assertion, that is supported by the data discussed earlier from adults with NAFLD in the WELCOME study (110), Nobili et al (130) found that in children with NAFLD, the presence of the PNPLA3 I148M gene polymorphism, may reduce the efficacy of DHA on fatty liver.…”
Section: Clinical Evidence In Children Populationmentioning
confidence: 81%